Impact of Previous Stroke on Short-Term Myocardial Reinfarction in Patients With Acute ST Segment Elevation Myocardial Infarction: An Observational Multicenter Study. Issue 6 (February 2016) - Tian, Li; Yang, Yanmin; Zhu, Jun; Liu, Lisheng; Liang, Yan; Li, Jiandong; Yu, Bo
Abstract : Abstract: Myocardial reinfarction is frequent after ST-elevation myocardial infarction (STEMI). The incidence of previous stroke in STEMI patients is also high. We aim to evaluate the risk factors for short-term myocardial reinfarction in STEMI patients in a multicenter study. STEMI patients with chest pain onset within 12 hours in 247 hospitals in China were enrolled. Seven and 30-day follow-ups from admission to hospitals were performed. The primary outcome of our study was myocardial reinfarction at 30 days after STEMI. The study population was stratified into 2 groups: STEMI patients with mayocardial reinfarction and without mayocardial reinfarction. Survival curve was constructed using Kaplan–Meier survival methods with log-rank statistics. Multivariable Cox regression model was performed to determine the risk factors for myocardial reinfarction events in STEMI patients. A total of 6876 STEMI patients were enrolled. The proportion of STEMI patients with previous stroke was 9.4%. Rate of 30-day myocardial reinfarction was 2.0% among all STEMI patients. Rate of 30-day myocardial reinfarction was 4.2% in STEMI patients with previous stroke which was statistically higher than that in STEMI patients without previous stroke ( P  < 0.001). Multivariable Cox regression analysis showed that previous stroke (HR, 3.673; 95% CI, 1.180–11.43) and statin use (HR, 0.230; 95% CI, 0.080–0.664) were independent predictors for 30-day myocardial reinfarction. A large proportion of STEMI patients had previous stroke history. Short-term myocardial reinfarction after STEMI is not infrequent. STEMI patients with previous stroke confronted higher rates of short-term myocardial reinfarction and statin could decline the risk of short-term myocardial reinfarction.